Evaluating the Effectiveness of Outpatient Rehabilitation Programs for Drug Users: A Case Study from South Sulawesi - Marzuki, Dian Saputra; Padilla, Nurul Aska; Razak, Amran; Prana Putra, Ryryn Suryaman (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Drug abuse is currently a major public health issue, with drug use considered one of the primary risk behaviors leading to the development of various problems. The establishment of primary clinics within the National Narcotics Agency (BNN) at the provincial, city, and district levels aims to maximize the reach of addicts and provide rehabilitation services, particularly outpatient rehabilitation. This study aims to evaluate the effectiveness of outpatient rehabilitation programs for drug users at the South Sulawesi Provincial National Narcotics Agency. Methods: This research employed an analytical observational design with a cross-sectional study approach. The population consisted of all outpatient rehabilitation clients at BNNP South Sulawesi, with a sample of 113 individuals selected using accidental sampling. Data were collected using questionnaires and observations. Data processing was conducted using Stata, and data analysis included univariate and bivariate analyses using the Chi-Square statistical test. The data presentation was provided in tables accompanied by narrative explanations. Results: The study revealed that 109 respondents (96.46%) rated the effectiveness of the drug rehabilitation program as good, while 4 respondents (3.54%) rated it as less effective. The statistical tests indicated significant relationships for program understanding (p = 0.000), goal achievement (p = 0.018), and tangible changes (p = 0.018). Conclusion: The Chi-Square test results for the variables of program understanding, goal achievement, and tangible changes yielded p-values < 0.05, leading to the rejection of H0 and acceptance of Ha. This indicates a significant relationship between these variables and the effectiveness of the drug rehabilitation program.